Soil Contaminant Concentrations at Urban Agricultural Sites in New Orleans, Louisiana - Kyle M. Moller; James G. Hartwell; Bridget R. Simon-Friedt; Mark J. Wilson; Jeffrey K. Wickliffe (Journal of Agriculture, Food Systems, and Community Development, 2018)
Along with the many benefits of urban agriculture comes the possible exposure to contaminants not typically seen in rural soils. Through the use of standard laboratory analyses (ICP-AES and CVAAS) and a field-portable X-ray fluorescence spectrometer (XRF) calibrated for soil analysis, this study quantified contamination levels at urban agricultural sites throughout New Orleans, Louisiana. The results of the standard laboratory analyses were compared to the results from the XRF.  We collected soil samples at 27 urban and suburban farm and garden sites from the Greater New Orleans area. We analyzed the soil samples for arsenic, cadmium, chromium, cobalt, copper, mercury, lead, nickel, and zinc using the XRF and standard methods. Most sites had median concentrations significantly below Louisiana’s soil standards. Paired soil samples showed XRF results were significantly higher than laboratory results for all metals but copper. Only lead (ρ=0.82, p<0.0001) and zinc (ρ=0.78, p=0.0001) were highly correlated. Poor correlation of results between XRF and standard methods make the standard methods preferred.